Women as a pathway: dilemmas of the Marriage Law in Northeast China in the early 1950s. Issue 2 (3rd April 2022) - Sui, Yi; Guo, Chao
ABSTRACT: As the first basic law of the People's Republic of China (PRC), the launching of the Marriage Law on May 1, 1950, was the Chinese Communist Party's (CCP) attempt to construct institutionalized and standardized criteria for social governance. However, tension between official reports and internal, confidential documents suggests that the implementation of the Marriage Law in Northeast China in the early 1950s confronted a series of difficulties. Due to the geographical and geopolitical distinctiveness of the region, the two priorities of the Northeast Bureau were the construction of heavy industry and support of the military during the Korean War (1950–1953). Within this context, frustrations with the Marriage Law were not simply a result of stubborn traditional opinions but reflected a conflict between different dimensions of modernity. Drafted before the founding of the PRC, the Marriage Law was representative of the party's legislative project on women's liberation, but local experiences eventually led to the Northeast Bureau's pragmatic operation on women's roles in the socialist regime. Under the varying forces constantly vying for control of women's bodies, the liberation of Chinese women was not so much the purpose as a means of achieving the CCP's project of nation-building.